Propagation of antiplane electroelstic wave signal in the piezoelectric layer taking into account large shears - A. S. Avetisyan; V. M. Khachatryan (National Academy of Sciences of Armenia)
In this work the propagation of finite amplitude electroelastic waves in dielectric layer of 6mm hexagonal symmetry class piezocrystal taking into account geometrical nonlinearity only in the form of large shears is investigated. It is shown that during the propagation of electroactive shear linear signal in adjoining mediums the related electromagnetoelastic wave field is arised and prime signal is hardly distored. The numerical analysis and comparison of distortion measure in the prime approximation of electroelastic field wave components is carried out. В работе рассматривается распространение электроупругих волн конечной амплитуды в диэлектрическом слое из пьезокристалла класса 6mm гексагональной симметрии с учетом геометрической нелинейности в виде только больших сдвигов. Показывается, что при распространении электроактивного сдвигового линейного сигнала в граничающих средах индуцируется связанное электромагнитоупругое волновое поле, а первичный сигнал сильно искажается. Проведен численный анализ и сравнение меры искажений в первом приближении волновых составляющих электроупругого поля.
Keywords: Science; Physics